2018
DOI: 10.1038/s41424-018-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress as a biomarker for monitoring treated celiac disease

Abstract: IntroductionHigh levels of reactive oxygen species (ROS) and impaired antioxidant defense systems lead to oxidative stress (OxS) and tissue injury in different intestinal and extra intestinal conditions, including celiac disease (CD). The aim of the present study was to investigate the role and potential use of ROS and other biomarkers of OxS in the clinical management of CD.MethodsWe collected duodenal specimens and blood samples from naïve patients (N-CD), patients on a gluten free diet (GFD) including respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 49 publications
1
36
0
2
Order By: Relevance
“…Oxidative stress and consequent accumulation of damaged intracellular macromolecules [ 19 , 20 ] are important components of mucosal deterioration and increased intestinal permeability of patients with CD [ 21 ]. Recently, Moretti et al reported that the production of ROS strictly correlates with the severity of intestinal damage; therefore, they recommended the routine determination of serum antioxidant capacity to monitor the efficiency of the gluten-free diet of patients with CD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and consequent accumulation of damaged intracellular macromolecules [ 19 , 20 ] are important components of mucosal deterioration and increased intestinal permeability of patients with CD [ 21 ]. Recently, Moretti et al reported that the production of ROS strictly correlates with the severity of intestinal damage; therefore, they recommended the routine determination of serum antioxidant capacity to monitor the efficiency of the gluten-free diet of patients with CD [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting topic is represented by the many different studies that pinpointed a tight correlation between oxidative stress, ASD and CD. The accumulation of reactive oxygen species (ROS), as well as the impairment of protective antioxidant systems, can lead to oxidative injury in many different circumstances, affecting intestinal and extra intestinal areas [ 120 ], so that some authors speculated about the use of oxidative stress biomarkers for the management of CD. On the other hand, recently Waligora et al have taken into account that neurological modifications occurring in ASD, such as intensity of emotional and behavioral symptoms, might be ascribed to oxidative damage [ 121 ] and considered ROS and biomarkers of oxidative stress as potential metabolic indicators for the development of appropriate programs of pharmacological therapy.…”
Section: Oxidative Stress Hypothesismentioning
confidence: 99%
“…These counter mechanisms describe the general processes that govern redox control. Moreover, the lack of redox control in the form of prolonged oxidative or reductive stresses has been linked to several disease states [117][118][119] including cardiovascular diseases.…”
Section: Example 1: Finding the Relevant Concepts Of Differentmentioning
confidence: 99%